Stress testing household balance sheets in Luxembourg - Gastón Giordana; Michael Ziegelmeyer (European Central Bank (ECB), 2019)
This paper uses representative individual household data from Luxembourg to evaluate how severe economic conditions could affect bank exposure to the household sector. Information on household income, expenses and liquid assets are used to calculate household-specific probabilities of default (PD), aggregate bank exposure at default (EAD) and aggregate bank loss given default (LGD). The exercise is repeated with scenarios combining severe but plausible shocks to real estate prices, bonds and stocks, household income and interest rates. Compared to the no-shock baseline, the LGD rises by a multiple of eight, reaching 4.2% of total bank exposure to the household sector. The high-stress scenario also generates a relatively high percentage of defaults among socio-economically disadvantaged households. Our main conclusion is that bank losses appear to be quite sensitive to financial stress, despite three mitigating factors in Luxembourg: indebted households tend to hold liquid assets that can help smooth shocks, household leverage tends to decline rapidly once mortgages have been serviced several years, and loan-to-value ratios at origination appear not to be excessive.
Keywords: D10; D14; E44; G01; G21; 330; Financial stability; HFCS; Household finance